Does energy consumption and trade openness contribute to economic growth in the East Asian growth area? - Taasim, Shairil Izwan; Pinjaman, Saizal; Albani, Aliashim (EconJournals, 2021)
This paper attempts to investigate the energy consumption and trade openness by taking into consideration the economic growth among associations within countries of Asia. The database was constructed and restricted to a sub-region area in southeast Asia well knows as Brunei, Indonesia, Malaysia, and the Philippines or BIMP-EAGA. The initiative, established in 1994 aims to increase the economic development of its members. We employed panel data analysis to examine the said linkage using panel co-integration on data taken for the period between 1970 to 2016. The approaches for panel data were the dynamic ordinary least squares (DOLS) and fully modified ordinary least squares (FMOLS). From our analysis, the findings indicated a significance and positive relationship between energy consumption, trade openness and economic growth. Additionally, we noted that both indicators are important among association to foster economic wellbeing. Furthermore, the benefit of this initiative of collaboration was highly successful.